The Effectiveness of Mentoring Cadres in Baby Care in Blang Bintang Sub-District, Aceh Besar, Indonesia - Anita Anita (Health Notions, 2019)
Introduction: A number of babies born in Aceh were 100,365 people in 2018. About 1,189 babies were declared dead. One of the ways to reduce mortality is that a cadres mentoring program has been carried out in rural villages. Purpose: To understand the effectiveness of cadre mentoring on baby care in Blang Bintang Sub-District, Aceh Besar District. Methods: The method of this study was a cross-sectional design. The population was 205 of the infants in Blang Bintang sub-district in 2018. Samples were infants